2014
DOI: 10.1038/ismej.2014.21
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale spatial patterns in bacterial community composition and function within freshwater ponds

Abstract: The extent to which non-host-associated bacterial communities exhibit small-scale biogeographic patterns in their distribution remains unclear. Our investigation of biogeography in bacterial community composition and function compared samples collected across a smaller spatial scale than most previous studies conducted in freshwater. Using a grid-based sampling design, we abstracted 100 þ samples located between 3.5 and 60 m apart within each of three alpine ponds. For every sample, variability in bacterial co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
81
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(88 citation statements)
references
References 56 publications
6
81
1
Order By: Relevance
“…Our results showed that spatial factors may either purely or accompanied with water chemistry play at least a minor role in determining bacterial community structures. As opposed to findings of Lear et al (2014) who stated that lentic bacterial communities in highly connected systems may be limited by dispersal when the distance between sites reaches 20 m, we found no definite signs for dispersal limitation of bacteria in our highly connected study system. By contrast, a large proportion of explained variation in bacterial communities was related to the pure effect of water chemistry, while spatial variables had only small effects on community structure.…”
Section: Drivers Of Community Structurecontrasting
confidence: 86%
See 1 more Smart Citation
“…Our results showed that spatial factors may either purely or accompanied with water chemistry play at least a minor role in determining bacterial community structures. As opposed to findings of Lear et al (2014) who stated that lentic bacterial communities in highly connected systems may be limited by dispersal when the distance between sites reaches 20 m, we found no definite signs for dispersal limitation of bacteria in our highly connected study system. By contrast, a large proportion of explained variation in bacterial communities was related to the pure effect of water chemistry, while spatial variables had only small effects on community structure.…”
Section: Drivers Of Community Structurecontrasting
confidence: 86%
“…Our results largely support the importance of local environmental conditions as water chemistry variables explained a relatively large proportion of variation in bacterial community structure at the three taxonomic levels we studied. However, there is evidence that spatial processes (Reche et al, 2005;Lear et al, 2014), temporal variation of different assembly mechanisms related to abiotic factors (Langenheder et al, 2012) and the occurrence of a keystone predator (Berga et al, 2015) may also affect bacterial community structures. Our results showed that spatial factors may either purely or accompanied with water chemistry play at least a minor role in determining bacterial community structures.…”
Section: Drivers Of Community Structurementioning
confidence: 98%
“…Unsurprisingly, most abundant bacteria appeared to be habitat generalists in our study, given that 98% of abundant OTUs occupied 450% of sites. Similarly, Lear et al (2014) found that the regional factors explained the largest proportion of variation of bacterial community composition in the ponds that are connected to each other by ephemeral channels. These authors suggested that large numbers of immigrant taxa are received by each pond that could enhance the connection between community composition and regional factors.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Lindström and Langenheder (2012) depicted the relationship between regional and local factors along gradients of dispersal rate and selective strength. It has been suggested that the nature of bacterial communities is important in the creation of wider biogeographical patterns as the dispersal potential could affect the connection between community composition and local and regional factors (Lindström and Langenheder, 2012;Lear et al, 2014). The most abundant bacteria can disperse readily as there are, by definition, many more individuals that can potentially be involved in a dispersal event.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, unveiling the mechanisms that regulate and maintain this diversity, microbial community assembly, distribution and variation is of fundamental interest in marine ecology. The existence of microbial biogeographic patterns is well established and it has been studied extensively in aquatic systems during the past few decades on various spatial scales [11,22,23,28]. A common understanding is that bacterial community similarity is decreasing with increasing geographic distance referred to as "distance-decay" relationship.…”
Section: Introductionmentioning
confidence: 99%